Analysis of leaf forage value and screening of different populations of Pteroceltis tatarinowii, a rare and endemic species in China - Gao, Yun; Cheng, Tian-Tian; Zhang, Chun-Xiang; Yan, Yu; Zhang, Lin; Liu, Qing-Zhong; Liu, Yan; Qiao, Qian (Frontiers in Plant Science, 2023)
To fully exploit the economic value of the Chinese endemic species Pteroceltis tatarinowii and provide new resources for forage production, the forage nutritional values of P. tatarinowii leaves from different populations were analysed and evaluated. The results were as follows: 1) there were significant differences in the forage nutrient indices of the leaves from different populations. The crude protein content was 10.77%-18.65%, at an average of 14.58%. The average crude fat content was 6.79%; the average crude fiber content was 7.62%; the average content of neutral detergent fiber was 25.33%; and the average content of acid detergent fiber was 17.52%. The average phosphorus and calcium contents in leaves were 0.785 g·kg-1 and 58.01 g·kg-1, respectively. The tannin content was much lower than the antifeedant standard, at an average of 4.97 g·kg-1. Thus, P. tatarinowii leaves have high contents of crude protein, crude fat and calcium and a low content of fiber and tannins, which provide a material basis for this species to develop into an excellent woody forage tree. 2) There were significant differences in the forage quality evaluation indices among the populations. The forage indexes of NDP, ADP, DMI, DDM and RFV of 21 populations all met the super standard of AFGC for hay; 2 crude protein indices met the grade 1 standard; and 12 crude protein indices met the grade 2 standard. Four high-protein and high-RFV forage populations, SDJN, SDZZ, SXLQ and AHXX, were selected. 3) The results of the correlation analysis showed that there was no significant geographical variation trend. However, the forage characteristics had as strong correlation with altitude, average annual temperature and annual precipitation. Thus, high altitude, low temperatures and rainy weather can improve the forage value of leaves. At the same time, the forage value of P. tatarinowii leaves can be further improved by increasing nitrogen fertilizer and reducing K fertilizer and Ca fertilizer during cultivation. 4) Cluster analysis showed obvious regionalism. Taking the Yangtze River Basin as the limit, cluster analysis divided the species into four populations groups, namely, the Yangtze River Basin populations, northern populations, southwestern populations and eastern coastal populations.